Micro/Meso Mechanical Manufacturing (M4): opportunities and challenges: a review - Reyad, Mehfuz; Ali, Mohammad Yeakub (2006)
Besides conventional precision manufacturing and micro-electro-mechanical system (MEMS), micro/meso mechanical manufacturing (M4) is emerging as the most potential contender to fabricate complex micro/meso-scale components using a variety of engineering materials.M4 domain will cover the components sizes from 10 to 104μm which is inconvenient to fabricate by other processes. Moreover, the inclusion of ‘microfactory’ concept in manufacturing micro/meso-scale parts shows huge prospects in terms of low power consumption, reduced space requirement and higher production. This paper presents the opportunities of this new approach of manufacturing along with the review of the recent efforts in M4, especially for micro-end-milling process.